2015
DOI: 10.1089/jmf.2015.3448
|View full text |Cite
|
Sign up to set email alerts
|

Milk Collected at Night Induces Sedative and Anxiolytic-Like Effects and Augments Pentobarbital-Induced Sleeping Behavior in Mice

Abstract: Milk has long been known and used to promote sleep. The sleep-promoting effect of milk has been attributed to its psychological associations (i.e., the memory of a mother giving milk at bedtime) and its rich store of sleep-promoting constituents (e.g., tryptophan). Studies have shown that milk harvested at night (Night milk) contains exceptionally high amounts of tryptophan and melatonin. In the present study, we evaluated the psychopharmacological properties of Night milk, particularly its probable sleep-prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…To further corroborate the potential sleep-inducing effects of nighttime milk, another study showed that melatonin-enriched milk improved sleep efficiency and reduced the number of awakenings in middleaged adults diagnosed with insomnia (49). Nighttime milk, which is abundant in Trp and melatonin, shortens the onset and prolongs the duration of sleep in mice (50) and has a sedating effect. In mice, motor balance and coordination are reduced to a level comparable to known sedatives with the administration of nighttime milk.…”
Section: Sleep-promoting Foods and Sleep Quality: Experimental Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further corroborate the potential sleep-inducing effects of nighttime milk, another study showed that melatonin-enriched milk improved sleep efficiency and reduced the number of awakenings in middleaged adults diagnosed with insomnia (49). Nighttime milk, which is abundant in Trp and melatonin, shortens the onset and prolongs the duration of sleep in mice (50) and has a sedating effect. In mice, motor balance and coordination are reduced to a level comparable to known sedatives with the administration of nighttime milk.…”
Section: Sleep-promoting Foods and Sleep Quality: Experimental Findingsmentioning
confidence: 99%
“…An analysis of milk content in one study revealed that nighttime milk contained higher amounts of Trp (4.66 mg/g) and melatonin (85.5 pg/g) than daytime milk (3.75 mg/g and 8.8 pg/g, respectively) (50). Another study used nighttime milk with a melatonin concentration of 10.2-18.3 pg/mL, with subjects consuming 0.5 L milk/d (41).…”
Section: Sleep-promoting Foods and Sleep Quality: Experimental Findingsmentioning
confidence: 99%
“…We are currently performing the latter in keeping with our long-standing interest to determine genetic biomarkers of ADHD behaviors (dela Peña et al 2015a(dela Peña et al ,2015b. Identification of these genes was facilitated through selection of common DEGs in the PFC of hyperactive SHR/NCrl vs. WKY/NCrl and Wistar control rats and further validations of the differential expression levels of these genes in drug-naïve SHR/NCrl and also in AMPH-treated SHR/NCrl which showed attenuated locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…these genes in the PFC of control strains thereby increasing their activity may further verify the involvement of these genes in mediating hyperactivity in SHR/NCrl. We are currently performing the latter in keeping with our long-standing interest to determine genetic biomarkers of ADHD behaviors (dela Peña et al 2015a(dela Peña et al ,2015b. Of interest, although outside of the scope of this study, identifying AMPH-regulated genes in the PFC of WKY/NCrl and Wistar rats which showed locomotor sensitization to AMPH may help determine candidate genes that mediate such behavioral effect of AMPH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation